The Little Mermaid: Equality of Race and Skin Color to Criticism of Disney Film Fans on Twitter - Asrul Nur Iman; Dzakiyyah Dzikraa Paokuma; Elsa Hidayati; Silvi Ramawati (Dinasti Publisher, 2024)
The animated film The Little Mermaid, adapted by Walt Disney in 1989, is a heartwarming tale about a mermaid named Ariel who falls in love with a prince. Social media users, mainly young adults, have noticed that the film touches on issues related to race and ethnicity. This study utilizes a content analysis method with a qualitative approach to explore the messages of equality that Disney conveys through the film. By examining fan comments, scenes, dialogue, and various forms of media such as images and text, we tried to uncover how Disney promotes equality in The Little Mermaid. Based on findings, Disney enthusiasts expressed disappointment with the company's failure to meet their expectations, particularly about Princess Ariel's depiction of dark skin. Detractors went so far as to make disparaging remarks, suggesting that black individuals were viewed as inferior and unequal to their white counterparts. Consequently, Disney's attempt to promote messages of fairness and equality was met with controversy among its devoted fan base.